Iceland : Staff Report for Second Review Under Stand-By Arrangement and Request for Extension of the Arrangement, Rephasing of Access and Establishment of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2010)
This report discusses Iceland's Second Review under the Stand-By Arrangement and Request for Extension of the Arrangement. Supportive fiscal policies have helped consumption hold up better than expected, while the external sector has benefited from currency depreciation and higher commodity prices. The overall improvements in inflation and the trade and current account balances since the late 2008 crisis have been striking. Indicators suggest firming consumer sentiment, and stable inflation expectations, but still weak business sentiment.